The NASA High-Resolution Speckle Interferometric Imaging Program: Validation and Characterization of Exoplanets and Their Stellar Hosts - Howell, Steve B.; Scott, Nicholas J.; Matson, Rachel A.; Everett, Mark E.; Furlan, Elise; Gnilka, Crystal L.; Ciardi, David R.; Lester, Kathryn V. (Frontiers in Astronomy and Space Sciences, 2021)
Starting in 2008, NASA has provided the exoplanet community an observational program aimed at obtaining the highest resolution imaging available as part of its mission to validate and characterize exoplanets, as well as their stellar environments, in search of life in the universe. Our current program uses speckle interferometry in the optical (320-1000 nm) with new instruments on the 3.5-m WIYN and both 8-m Gemini telescopes. Starting with Kepler and K2 follow-up, we now support TESS and other space- and ground-based exoplanet related discovery and characterization projects. The im- portance of high-resolution imaging for exoplanet research comes via identification of nearby stellar companions that can dilute the transit signal and confound derived exoplanet and stellar parameters. Our observations therefore provide crucial information allowing accurate planet and stellar properties to be determined. Our community program obtains high-resolution imagery, reduces the data, and provides all final data products, without any exclusive use period, to the community via the Exoplanet Follow-Up Observation Program (ExoFOP) website maintained by the NASA Exoplanet Science Insti- tute. This paper describes the need for high-resolution imaging and gives details of the speckle imaging program, highlighting some of the major scientific discoveries made along the way.